The effect of aspirations on agricultural innovations in rural Ethiopia - Daniel Ayalew Mekonnen; Nicolas Gerber (University of Bonn, Center for Development Research (ZEF), 2016)
This paper identifies the effect of aspirations on the adoption of agricultural innovations in the context of rural Ethiopia. While most studies on agricultural innovations have focused on identifying observable and resource-related deprivations or 'external' constraints, a related stream of literature suggests that 'internal' constraints, such as the lack of aspirations, could reinforce external constraints and lead to self-sustaining poverty traps. Since both aspirations and the adoption of innovations are forward-looking, they are likely to be intimately linked. Aspirations are motivators that can enhance innovations or their adoption not only in their own right but also through their determinants, including self-efficacy, locus of control and other internal traits that may be unobserved. This implies that aspirations may affect innovations through multiple channels and hence may be endogenous. On the other hand, aspirations are also affected by a person's level of achievement, implying that aspirations and innovations are simultaneously determined. To identify the effect of aspirations on the adoption of agricultural innovations, we conducted both plot-level and household-level analysis using purposely collected data from households in rural Ethiopia. Using econometric strategies that account for the endogenous nature of aspirations, we found that a narrow or a very wide gap between aspirations and achievement in a farming household is strongly associated with low levels of innovativeness and low adoption rate of innovation products such as chemical fertilizers.
Keywords: D1; O1; Q1; Q12; Q16; 330; Aspirations; innovations; agriculture; Ethiopia